Gonadotrope-specific deletion of the BMP type 2 receptor does not affect reproductive physiology in mice. Issue 3 (13th November 2019) - Ongaro, Luisina; Zhou, Xiang; Cui, Yiming; Boehm, Ulrich; Bernard, Daniel J
Abstract: Activins selectively stimulate follicle-stimulating hormone (FSH) secretion by pituitary gonadotrope cells. More recently, other members of the TGFbeta superfamily, the bone morphogenetic proteins (BMPs), were reported to regulate FSH synthesis. Activins and BMPs independently and synergistically stimulate transcription of the FSHbeta subunit ( Fshb ) gene in immortalized gonadotrope-like cells. Both ligands can signal via the activin receptor type IIA (ACVR2A) to regulate FSH synthesis in vitro. In vivo, global Acvr2a knockout mice exhibit a 60% reduction in circulating FSH relative to wild-type animals, suggesting that activins, BMPs, or related ligands might signal through additional type II receptors to regulate FSH in vivo. Although the leading candidates are ACVR2B and the BMP type II receptor (BMPR2), only the latter mediates activin or BMP2 induction of Fshb transcription in vitro. Here, we generated mice carrying a loss of function mutation in Bmpr2 specifically in gonadotropes. Puberty onset, estrous cyclicity, and reproductive organ weights were similar between control and conditional knockout females. Serum FSH and luteinizing hormone (LH) and pituitary expression of Fshb and the LHbeta subunit ( Lhb) were similarly unaffected by the gene deletion in both sexes. These results suggest that BMPR2 might not play a necessary role in FSH synthesis or secretion in vivo or that another type II receptor, such as ACVR2A, can fully compensate for its absence. These data also further contribute to the emerging concept that BMPs may not be physiological regulators of FSH in vivo. Abstract : Ablation of BMPR2 in gonadotropes does not affect gonadotropin levels, suggesting that TGFbeta ligands other than BMPs and activins may be the primary regulators of FSH synthesis in mice.